Potentially inappropriate medication among older patients with diabetic kidney disease - Wang, Yuping; Zhu, Jie; Shan, Luchen; Wu, Ling; Wang, Cunchuan; Yang, Wah (Frontiers in Pharmacology, 2023)
Objective: Potentially inappropriate medications (PIM) contribute to poor outcomes in older patients, making it a widespread health problem. The study explored the occurrence and risk factors of PIM in older diabetic kidney disease (DKD) patients during hospitalization and investigated whether polypharmacy was associated with it. Methods: Retrospective analysis of the patients ≥ 65 years old diagnosed with DKD from July to December 2020; the PIM was evaluated according to the American Beers Criteria (2019). Factors with statistical significance in univariate analysis were included in Logistic multivariate analysis to explore the potential risk factors related to PIM. Results: Included 186 patients, 65.6% of patients had PIM, and 300 items were confirmed. The highest incidence of PIM was 41.7% for drugs that should be carefully used by the older, followed by 35.3% that should be avoided during hospitalization. The incidence of PIM related to diseases or symptoms, drug interactions to avoid, and drugs to avoid or reduce dose for renal insufficiency patients were 6.3%, 4.0% and 12.7%, respectively. The medications with a high incidence of PIM were diuretics (35.0%), benzodiazepines (10.7%) and peripheral ɑ1 blockers (8.7%). Compared with hospitalization, there were 26% of patients had increased PIM at discharge. Multivariate Logistic regression analysis showed that polypharmacy during hospitalization was an independent risk factor for PIM, OR = 4.471 (95% CI: 2.378, 8.406). Conclusion: The incidence of PIM in hospitalized older DKD patients is high; we should pay more attention to the problem of polypharmacy in these patients. Pharmacists identifying the subtypes and risk factors for PIM may facilitate risk reduction for older DKD patients.